Principal’s Management in Improving Teacher’s Professionalism - Triokoyulisma, Triokoyulisma; Fitria, Happy; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2024)
Leadership management involves planning, organizing, directing, and supervising the efforts of members of an organization to achieve goals. Principal management is crucial in creating teaching and learning situations for teachers and students. They provide guidance, assistance, supervision, and assessment on technical implementation and development of teaching education programs. Teachers play a significant role in influencing the quality of education, and professionalization of teachers is essential for optimal service delivery. However, many teachers struggle with pedagogical competence, mastering teaching material, and presenting meaningful learning activities. Additionally, the school principal’s busy life often prevents proper implementation of guidance and supervision, resulting in teachers not showing expected professionalism. Research is needed to address these issues. This research was conducted at SMA Negeri 3 Banyuasin III, Banyuasin Regency, South Sumatra Province. The object of this research is the principal’s management in improving teacher professionalism at SMA Negeri 3 Banyuasin III. This research uses a descriptive paradigm approach with qualitative research methods. The data in this research was collected through observation, interviews, and documentation. The researcher found that the principal at SMA Negeri 3 Banyuasin III has been effective in increasing teacher professionalism through planning, organizing, implementing, and supervising. They provide guidance, opportunities for self-development, and support for teachers’ activities. However, challenges include the incompatibility of scientific background with the field, teachers’ low interest in self-development, lack of understanding of curriculum content, low use of technology, and low awareness of individual teachers’ duties.